(untitled) (Research, Society and Development, 2022)
Sedimentary deposits of soft soils occur on the Brazilian coast. These soils usually have high organic matter content, high compressibility, low permeability and shear resistance. They are problematic soils for use and occupation. The alluvial plain of marine fluvial origin in the city of Recife, presents more than 50% of its area with soft clays. The article evaluates the stress-strain-resistance behavior of soft organic clay located in the northern region of the city of Recife-PE, Brazil. In the field, undisturbed samples were collected and Piezocone and Vane tests were performed. In the laboratory, consolidation tests were carried out with vertical and horizontal drainage and triaxial. The influence of pre-drying in determining the consistency limits was analyzed and quality of the samples at pre-consolidation stress. The soil profile presents a superficial layer of silty sand and sandy silt followed by layers of very soft alluviums with the presence of peat and clay, of low resistance and high compressibility. The clay is slightly pre-compacted to a depth of 4.0 m and, after this depth, it is normally compacted. The relationship between the horizontal and vertical densification coefficient is 3.70. The samples show some dents. The average undrained resistance in the initial 4 m is 35 kPa and, in depth greater than 25 kPa. Clay is more sensitive in the initial 4.0 m. The undrained resistances obtained by laboratory tests (UU) are close to those obtained by peak vane tests.